Women's Disempowerment and Preferences for Skin Lightening Products That Reinforce Colorism: Experimental Evidence From India. (June 2021) - Adbi, Arzi; Chatterjee, Chirantan; Cortland, Clarissa; Kinias, Zoe; Singh, Jasjit
Global racism and colorism, the preference for fairer skin even within ethnic and racial groups, leads millions of women of African, Asian, and Latin descent to use products with chemical ingredients intended to lighten skin color. Drawing from literatures on the impact of chronic and situational disempowerment on behavioral risk-taking to enhance status, we hypothesized that activating feelings of disempowerment would increase women of color's interest in stronger and riskier products meant to lighten skin tone quickly and effectively. In two experiments (Experiment 1: N = 253 women and 264 men; Experiment 2: replication study, N = 318 women) with distinct samples of Indian participants, we found that being in a state of psychological disempowerment (vs. empowerment) increased Indian women's preference for stronger and riskier skin lightening products but not for milder products. Indian men's interest in both types of products was unaffected by the same psychological disempowerment prime. Based on these findings, we recommend increased consideration among teaching faculty, research scholars, and clinicians on how feeling disempowered can lead women of color to take risks to lighten their skin as well as other issues of intersectionality and with respect to colorism. We also encourage the adoption of policies aimed at empowering women of color and minimizing access to harmful skin lightening products.